2006
DOI: 10.1249/01.mss.0000218122.59968.eb
|View full text |Cite
|
Sign up to set email alerts
|

Energy Expenditure in Men and Women during 54 h of Exercise and Caloric Deprivation

Abstract: For both men and women, total energy expenditures were among the highest observed for a military FEX. TEE, when normalized or corrected to body mass and fat-free mass, and PAL were the same for men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 30 publications
1
26
0
1
Order By: Relevance
“…A study of Marine recruits participating in a demanding physically demanding 54 h training exercise also found that men and women performing similar high-intensity activities had similar weight-specific TEEs (men 350 AE 40 kJ/kg per day; women 340 AE 40 kJ/kg per day) [15]. Notably, the relative contribution of fat mass to TEE among the Norwegian cadets was nearly 90% in the women compared with 74% in the men, indicating marked sex differences in fat substrate utilization during this demanding training [6 ].…”
Section: Norwegian Ranger Trainingmentioning
confidence: 95%
See 1 more Smart Citation
“…A study of Marine recruits participating in a demanding physically demanding 54 h training exercise also found that men and women performing similar high-intensity activities had similar weight-specific TEEs (men 350 AE 40 kJ/kg per day; women 340 AE 40 kJ/kg per day) [15]. Notably, the relative contribution of fat mass to TEE among the Norwegian cadets was nearly 90% in the women compared with 74% in the men, indicating marked sex differences in fat substrate utilization during this demanding training [6 ].…”
Section: Norwegian Ranger Trainingmentioning
confidence: 95%
“…Study populations range from Norwegian cadets participating in a training course that involves a week of food and sleep deprivation and approximately 23 h/day of marching and other activities [4, 5,6 ], to soldiers participating in 8 weeks of physically demanding US Army Ranger training, in which sleep is restricted to 4 h/day and food is in short supply [7,8]. Others have studied long-range patrols by Swedish ski troops [9], hot weather training by Zimbabwean recruits [10], and a variety of other extremes [11][12][13][14][15] (see Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Nine further studies using ingestible sensors in sports or occupational settings involving physical activity were reviewed to assess the utility of the technology for field-based exercise applications. [24][25][26][27][28][29][30][31][32] From the outset, it should be noted that surprisingly few validation studies have delimited an acceptable level of agreement between methods. Gant et al 19 delimited a systematic bias of .0.1˚C between T intestinal and T rectal as being practically important in affecting decisions made on an individual's thermal status.…”
Section: Methodsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32] Table 4 illustrates these studies and indicates the increasing use of the technology with five of the nine studies published in 2006. [28][29][30][31][32] Six field-based studies have used ingestible sensors to measure T c during diverse sporting activities. 25 27 28 30-32 The studies provide unique and ecologically valid T c data and show the efficacy of the method, as all data were obtained during training sessions 27 31 or actual competitive events.…”
Section: Applications Of the Ingestible Temperature Sensormentioning
confidence: 99%
See 1 more Smart Citation